Des maisons hantées en Amérique au XIXe siècle - Stéphanie Sauget (Transatlantica)
Seen from the other side of the Atlantic Ocean, that a young country as the United States can have local stories of haunted houses can seem rather surprising, just as much as the still current attachment of the Americans in a kind of haunted “heritage”. The object of this article is to try to understand what haunts the American houses in the Nineteenth century, through the examination of famous cases, to examine the topography, to put them in connection with other contemporary phenomena and then to think about the construction of these narratives of “authentic” said haunted houses.